COMPRITOL® 888 LIPID MATRIX VIA TWIN SCREW EXTRUDER - Wadhwa, Abishek; Mathura, Vashish; Rathnanand, Mahalaxmi; Naha, Anup; Lewis, Shaila Angela (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this research was to explore the potential of Hot Melt Extrusion (HME) technique by using theophylline as the model drug to produce sustained release tablets utilizing Compritol®888 ATO as the retarding material and to study the influence of lipid: excipient ratio, excipient type as well as the processing conditions of the extruder on the release profile. Methods: The tablets prepared using hot fusion method was compared to the ones concocted by the HME technology. During the HME process, a powder mixture of moisture-free drug, lipid, and other adjuncts was introduced into the extruder and liquefied inside the barrel of the extruder. The in vitro dissolution studies of the formulations were carried out in pH 7.2 buffer using USP Apparatus 2. The extrudates were characterized via differential scanning calorimetry. Results: Comparing the two methods of processing, it was observed by the dissolution studies using phosphate buffer pH 7.2, that the tablets prepared by Hot Melt Extrusion method had a higher extent of release where all 3 formulations crossed 80% at the 8-hour mark, whereas the tablets prepared by hot fusion method did not show such consistency. Conclusion: This study demonstrated the fact that Compritol®888 ATO is a suitable waxy material that can be used as a matrix-forming agent to control the release of theophylline using the Hot Melt Extrusion process.